Identifying Grammatical and Mechanical Errors of Students’ Writing: Using “Grammarly” as an Online Assessment - Tira Nur Fitria (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
This research investigates “Grammarly” as one tool of an online assessment in identifying grammatical and mechanical errors of students in writing English. This research is descriptive qualitative research. The result analysis shows that Grammarly is used to assess the students’ writing both grammatical and mechanical (spelling, punctuation, and capitalization) errors. From Grammarly report, it represents the quality of writing.  First, student A’s text score is 46 out of 100. It is found writing issues (both grammatical and mechanical errors) such as confusing words, punctuation in compound/complex sentences, misspelled words, determiner use, incorrect verb forms, faulty subject-verb agreement, pronoun use, conjunction use, incomplete sentences also wordy sentences. Second, student B’s text score is 37 out of 100. It is found writing issues (both grammatical and mechanical errors) such as confusing words, misspelled words, determiner use, mixed dialects of English, incorrect noun numbers, pronoun use, incorrect verb forms, and comma misuse within clauses. Grammarly is an online proofreading service that checks for students’ grammar, spelling, and punctuation errors. Grammarly automatically verifies or detects the work typed based on a variety of factors and reveals a variety of student writing errors, both in terms of grammatical and mechanical. This finding suggests that teachers/lecturers can use Grammarly as online automated software to implement corrective evaluation of the EFL or non-EFL students’ writing. They can examine and analyze students' errors in great depth without having to make a lot of corrections or improvements manually.